Total cholesterol and Lipaemia Laborers in the height (La Oroya) - Kruger Porras, Francisco (1962)
A problem caused by the geography of Peru, among others, is the height. Much of our population lives several thousand meters above sea level in low barometric pressure and chronic anoxia, which impacts on your body produce organic and functional changes, making the man of the Andes corresponds to anthropological not found in other race, with innate and acquired characteristics that differentiate the inhabitant of the plain. Comparative studies between man and high sea level, remains inexhaustible field addressed primarily by Schools Monge, Hurtado Guzmán Barrón and other investigations.